Influence of Thermal Shocks on Residual Static Strength, Impact Strength and Elasticity of Polymer-Composite Materials Used in Firefighting Helmets - Pieniak, Daniel; Walczak, Agata; Oszust, Marcin; Przystupa, Krzysztof; Kamocka-Bronisz, Renata; Piec, Robert; Dzień, Grzegorz; Selech, Jarosław; Ulbrich, Dariusz (Materials, 2021)
The article presents results of experimental studies on mechanical properties of the polymer-composite material used in manufacturing firefighting helmets. Conducted studies included static and impact strength tests, as well as a shock absorption test of glass fiber-reinforced polyamide 66 (PA66) samples and firefighting helmets. Samples were subject to the impact of thermal shocks before or during being placed under a mechanical load. A significant influence of thermal shocks on mechanical properties of glass fiber-reinforced PA66 was shown. The decrease in strength and elastic properties after cyclic heat shocks ranged from a few to several dozen percent. The average bending strength and modulus during the 170 degree Celsius shock dropped to several dozen percent from the room temperature strength. Under these thermal conditions, the impact strength was lost, and the lateral deflection of the helmet shells increased by approximately 300%. Moreover, while forcing a thermal shock occurring during the heat load, it was noticed that the character of a composite damage changes from the elasto-brittle type into the elasto-plastic one. It was also proved that changes in mechanical and elastic properties of the material used in a helmet shell can affect the protective abilities of a helmet.